Aplicación de la técnica de sonido 360 para la producción de un cuento lojano; mediante un modelo de gamificación - Muñoz Campoverde, Karina Alexandra (2018)
Abstract:This project presents the production of the lojano story "A bet with the devil", in sound 360; through new techniques for capturing, reproducing, editing and synchronizing sound, used to create an enveloping auditory projection, capable of imitates the human ear. Gamification is also applied, which takes the process of gaming techniques as an essential tool to generate interactive dynamics that allow us to attract new users. The combination of the both techniques as the sound 360, and the gamification are reflected in the final result, with the elaboration of an audiogame, that is an attractive technological advance, where game situations are recreate and will be surpass due to use of the guidance of sound 360.